Incidence of bacterial pathogens in flying insects collected near poultry farms - A. Buyukyavuz; J.K. Northcutt; P.L. Dawson (Journal of Applied Poultry Research)
SUMMARY: Filth flies, especially house flies, can harbor and disseminate human pathogens to food and food contact surfaces. To determine the potential of flying insects to carry Salmonella and Campylobacter from poultry grow out houses, a total of 2,164 flying insects were caught and segregated based on flying insect family type and farm location in the Upstate, Middle, and Coastal parts of South Carolina in the United States for two 14-d sampling periods at 3 separate farms. Captured flying insects included house flies in the family Muscidae inside the poultry house (N = 289), house flies just outside the poultry house (N = 1023), and house flies 100 meters from the poultry houses (N = 547). Other flying insects included wasps in the family Vespidae species (spp.) captured just outside the poultry house (N = 71), Vespidae 100 meters from the poultry house (N = 126), flesh flies in the family Sarcophagidae just outside the poultry house (N = 13), and flesh flies 100 meters from the poultry house (N = 9), blow flies in the family Calliphoridae 100 meters from the poultry house, darkling beetles in the family Tenebrionidae just outside the poultry house (N = 30), and darkling beetles 100 meters from the poultry house (N = 56). Populations of Campylobacter spp., Salmonella spp., and total aerobic organisms (APC) were recovered from flying insects as well as the number of Salmonella spp. and Campylobacter spp. positive flying insects at a 100 m distance from the broiler farms. Along with insect groups, chicken feces in the grow-out houses from 3 farms, cow manure around farm 1 and farm 2, and dog feces around farm 1 were also sampled. While no Campylobacter jejuni was recovered from any of the samples, including flying insect groups, chicken feces, cow manures, and dog feces, Campylobacter coli positive samples were detected in the cow manure samples in both collection periods, 100m-Calliphoridae, out-house flies and 100m-darkling beetles in 1 out of 2 collection periods on farm 2. Moreover, positive Serogroup B Salmonella spp. were detected in the groups in-chicken feces, in- house flies, and out- house flies on farm 2 and positive Serogroup C Salmonella spp. were detected in the groups of in- chicken feces, out- house flies, and 100m- house flies on farm 3. These data suggest that house flies may be a vector in the transmission of Salmonella spp. to and from broiler farms.